Prevention strategis of unplanned pregnancies among adolescents: A systematic review - Neda Nik khesa; Roghayieh Nourizadeh; Saeed Dastgiri; Esmat Mehrabi (Payesh, 2018)
Objective (s): Unwanted pregnancies and sexual health problems, and consequently illicit abortions and sexually transmitted diseases, may also occur among adolescents. Therefore, in the present study, we investigated various interventions that were used in studies to prevent unwanted pregnancy among adolescents through a systematic review. Methods: An extensive literature search was conducted using the Google Scholar, Cochran Library, SID, Magiran, Web of Science, Scopus, Pubmed, e-learning databases on clinical trials conducted during 1990 and 2018. To evaluate the quality of the studies, the Cochran tools for RCT were used. Finally, 15 studies were selected for systematic review. Results: Overall, based on findings from the review of related articles, interventions to reduce unplanned pregnancies in adolescents were categorized as follows: (i) interventions focusing on contraceptive methods, (ii) interventions focusing on the impact of preventive training including health education, individual and group counseling and parent education, (iii) multiple interventions that included a combination of interventions focusing on promoting contraceptive methods and preventive training. Conclusion: Evidence provided by this  ystematic reiew supports the use of educational and preventive interventions focusing on multiple interventions to reduce adolescent pregnancies, but there is a need for a proper framework, infrastructure, and resources for the success of these interventions.